Ultrasound Elastography in Evaluation of Peripheral Pulmonary Lesions - Rouf, Abdul; Debi, Uma; Devkota, Shritik; Garg, Mandeep; Singh, Navneet; Bal, Amanjit; Bhujade, Harish; Prasad, K. T. (Acta medica Lituanica, 2026)
Background: Differentiating benign from malignant peripheral pulmonary lesions (PPLs) remains a clinical challenge, especially in resource-limited settings. While computed tomography is the standard imaging modality, it involves radiation exposure and often lacks specificity. Shear Wave Elastography (SWE) is a non-invasive ultrasound technique that quantifies tissue stiffness and may aid in the evaluation of PPLs. Methods: In this prospective observational study, 42 patients with peripheral pulmonary lesions underwent transthoracic SWE prior to histopathological evaluation. Elastography values were compared between benign and malignant lesions. Statistical analysis included ROC curve assessment, logistic regression, and correlation with histopathological and microbiological outcomes. Results: Of the 42 patients, 64.3% had malignant and 35.7% had benign lesions. The mean SWE value for malignant lesions was significantly higher (6.82 ± 2.27 kPa) than for benign lesions (3.72 ± 2.23 kPa; p <0.001). The AUROC for mean SWE values in predicting malignancy was 0.849 (95% CI: 0.713–0.986), demonstrating good diagnostic performance with statistically significant difference (p = <0.001), with a cutoff of ≥4.8 kPa yielding 85% sensitivity and 80% specificity. Squamous cell carcinoma exhibited the highest stiffness among malignancies. Certain benign lesions, particularly tuberculosis, showed elevated stiffness, resulting in false positives. Logistic regression identified mean SWE as an independent predictor of malignancy (OR = 2.11, p = 0.030). Conclusion: Transthoracic SWE is a non-invasive, radiation free and promising tool for evaluating PPLs, offering good diagnostic accuracy in distinguishing malignant from benign lesions. It holds particular promise in settings where access to advanced imaging or biopsy is limited, and may assist in triaging patients for early tissue diagnosis.